Hubungan Minat Baca Terhadap Kemampuan Membaca Pemahaman Pada Cerita Fiksi Siswa Kelas V SDN Gugus 5 Cakranegara - Nurlelah, Nurlelah; Istiningsih, Siti; Setiawan, Heri (Jurnal Ilmiah Mandala Education (JIME), 2022)
This study aims to determine the relationship between reading interest (X) and reading comprehension skills in fiction (Y) in class V students of SDN Gugus 5 Cakranegara. This research is a quantitative research with the type of correlational research. Sampling was done by random sampling technique with a total sample of 78 students. The data collection uses a questionnaire for the variable of reading interest and a multiple choice test for the variable of reading comprehension ability in fiction stories. Data analysis used data prerequisite test and hypothesis testing. The data prerequisite test used the normality test of the data and the linearity test of the data, while the hypothesis test used the pearson product moment correlation. The results showed that there was a relationship between reading interest and reading comprehension ability in class V students of SDN Gugus 5 Cakranegara. The value of the correlation coefficient or rcount of 0.335 is greater than rtable of 0.223 (0.335 > 0.223) with a significance level of 5% and a coefficient of determination value of 11.22%. There is a correlation between reading interest and reading comprehension ability in fiction stories, it is hoped that teachers and parents can raise students' awareness of reading and increase students' reading interest so that students' reading comprehension skills increase, so that it can be ascertained that the learning outcomes they have will be better.